Culturally based semantic losses in Lonely Planet’s travel guides translations for Beijing, Shanghai, and Sichuan - Chen, Shiyue; Zhou, Tianli (Frontiers in Communication, 2024)
Translating cultural references in tourism materials is pivotal in bridging cultural gaps and facilitating cross-cultural communication. Despite the escalating demand for accurate translation, no research exists to address the losses in cultural connotations and their impact on semantic accuracy in Chinese-English cultural reference translation within Lonely Planet's travel guides. This research seeks to fill this gap, specifically focusing on Beijing, Shanghai, and Sichuan destinations. The objectives are as follows: 1) to identify the types of cultural connotation losses in the English translation of Chinese cultural references; 2) to examine cultural-related semantic losses, considering instances where cultural connotation losses lead to partial or complete semantic losses; and 3) to elucidate the translation decisions (both macro and micro levels) implications on the culturally based semantic losses. A qualitative-descriptive approach forms the foundation of this research. The findings revealed seven types of cultural connotation losses, with partial semantic losses predominant. Applying Venuti's domestication and foreignization, the results also uncovered a strong inclination toward foreignization, emphasizing the strangeness inherent in the source culture is intensified. These findings contribute to a nuanced understanding of the complexities of translating cultural connotations and maintaining semantic accuracy, offering a comprehensive typology that can guide future translation practices and serve as a springboard for further research in the field. Lastly, this study underscores the significance of maintaining cultural connotations in translation, thereby contributing to the ongoing development of cross-cultural communication.